Role of Escherichia coli P fimbriae in intestinal colonization in gnotobiotic rats. - Herías, M V (1995)
Adherence via P fimbriae is associated with long-term persistence of Escherichia coli in the human large intestine, but a causal relationship has not been proven. In the present study, germfree rats were colonized with a mixture of two isogenic E. coli strains, one P fimbriated and the other type 1 fimbriated. Both types of fimbriae conferred adherence to rat colonic epithelial cells. With two mutant strains from a pyelonephritogenic isolate of serotype O75:K5:H-, the P-fimbriated strain 824 attained much higher numbers than its type 1-fimbriated counterpart when colonized in vivo for 2 weeks (10(10) versus 10(6) bacteria per g, respectively; P < 0.0001). The expression of P fimbriae by 824 was also retained during colonization. With transformant isogenic strains obtained from a normal fecal isolate incapable of phase variation, no benefit of P fimbriae was seen and most bacteria lost their plasmids during in vivo colonization. When the pyelonephritogenic mutant and fecal transformant strains were combined, the former colonized at high levels while the latter were suppressed. In contrast, no suppression was seen when the transformant E. coli strains colonized in combination with Lactobacillus acidophilus or Peptostreptococcus sp. The results indicate that P fimbriae, but also other bacterial traits linked to uropathogeneicity, could play an important role for persistence in the gut normal microbiota. Neither P nor type 1 fimbriae seemed to contribute to the ability to translocate to the mesenteric lymph nodes.